Contextual learning in the education unit level curriculum faces obstacles - Titus Do Amar; Sarma Haning (Trigin Institute, 2022)
This study examined Indonesia's education unit level adoption of the Contextual Teaching and Learning approach and its supportive and limiting elements. In the Education Unit Level Curriculum, Contextual Teaching and Learning works well. To make learning more relevant and the Education Unit Level Curriculum implementation successful, implementation must be context-based. The Unit Level Curriculum must match students, educators, learning media, the environment, and their natural traits. Because this must follow the method to attain educational goals. Thus, Contextual Teaching and Learning depends on the Education Unit Level Curriculum. To support and balance each other, the Unit Level Curriculum socialization process for instructors must function properly. If the Education Unit Level Curriculum implementation goes successfully, the Contextual Teaching and Learning approach will be the same